SURICATA ACCURACY OPTIMIZATION BASED ON LIVE ANALYSIS USING ONE-CLASS SUPPORT VECTOR MACHINE METHOD AND STREAMLIT FRAMEWORK - Agus Ariwanta, I Putu Yesha; Ernanda Aryanto, Kadek Yota; Gunadi, I Gede Aris (Informatika, Universitas Jenderal Soedirman, 2024)
Based on data from the Checkpoint website, there are more than 10 million cyber-attacks in a single day, and the top sequence of this cyber-attack is evident in educational institutions. The IT unit of Kartini Bali Health Polytechnic has not yet conducted testing for accuracy and speed to detect suspicious activities on the computer network. The implementation of network security systems that have not undergone testing will undoubtedly have a negative impact on system providers and users. The application of Live Analysis based on a website and the One-Class Support Vector Machine (SVM) is used to optimize the capabilities of the Suricata in detecting suspicious activities on computer networks and providing visual and real-time reports. This research utilizes the Suricata for optimizing the computer network security system, with the researcher using the Streamlit Framework for Live Analysis based on a website and the One-Class Support Vector Machine (SVM) for classifying log data and visual reporting. For testing the computer network security system, tools such as Nmap, Loic, and Brutus are used. The results of the research using the One-Class Support Vector Machine (SVM) in detecting three types of attacks Port Scanning, DDOS Attack, and Brute Force Attack, show an accuracy value of 96%, precision of 95%, recall of 96%, and F1-Score of 95%. In the performance and load testing of the live analysis system using the Streamlit framework, the results show that the developed system is responsive, with CPU usage at 38%, memory usage at 62.3%, and an average system load time of 5 milliseconds.